1997
DOI: 10.1007/bf02977032
|View full text |Cite
|
Sign up to set email alerts
|

Characterizations of intervals via continuous selections

Abstract: Abstract. We prove that: (i) a pathwise connected, Hausdorff space which has a continuous selection is homeomorphic to one of the following four spaces: singleton, [0, 1), [0,1] or the long line L, (ii) a locally connected (Hausdorff) space which has a continuous selection must be orderable, and (iii) an infinite connected, Hausdorff space has exactly two continuous selections if and only if it is compact and orderable. We use these results to give various characterizations of intervals via continuous selectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…According to [10,Lemma 7.2], T f is also an order topology on X provided X is connected. Finally, by [12,Theorem 4 and Remark 16], T f coincides with the original topology on X provided X is connected and locally connected.…”
Section: Introductionmentioning
confidence: 88%
“…According to [10,Lemma 7.2], T f is also an order topology on X provided X is connected. Finally, by [12,Theorem 4 and Remark 16], T f coincides with the original topology on X provided X is connected and locally connected.…”
Section: Introductionmentioning
confidence: 88%
“…Building on work of G. Artico, U. Marconi, J. Pelant, L. Rotter and M. Tkachenko [1], S. García Ferreira and M. Sanchis [7] showed that a pseudocompact space X admits a continuous weak selection if and only if theČech-Stone compactification βX is orderable, and consequently, if and only if X is suborderable (or a GO-space). Improving on Michael's result stated above, T. Nogura and G. Shakhmatov proved in [16] that a locally connected space X admits a continuous weak selection if and only if it is orderable. Recently, V. Gutev and T. Nogura [11], in a very nice survey article on the selection problem, restated van Mill-Wattel's question and asked, in particular, whether a locally compact space admitting a continuous weak selection is weakly orderable.…”
mentioning
confidence: 87%
“…However, in case of connected spaces, this is so. The following result is a partial case of [7, Lemmas 7.2 and 7.3] (see also [9,Lemma 10]). …”
Section: Selections and Order-like Relationsmentioning
confidence: 98%